Analisis Pelaksanaan Asesmen Autentik dan Berpikir Kritis Selama Pembelajaran Daring - Afrizal, Stevia Rafie (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2022)
This study aims to determine how the implementation of authentic assessment and critical thinking in a school in the city of Semarang. This type of research is descriptive qualitative. This research was conducted at SMA Negeri 3 Semarang. The subjects of this study were the biology teacher at the high school and the students. The focus of this research is to analyze the implementation of authentic assessments and critical thinking during online learning based on the 2013 curriculum. The data collection techniques used are interview techniques for biology teachers, interviews with several students from class XI and XII, observation, and analyzing learning tool documents such as lesson plans and lesson plans. LKPD. The results showed that in the implementation of an authentic assessment of Biology material for class XI and XII at SMA Negeri 3 Semarang during online learning experienced several obstacles from both students and teachers. In addition, the tests and worksheets given by the teacher are indicators of critical thinking.